Beyond baby blues: a campaign to raise awareness on postpartum depression among mothers in Singapore - Ong, Celine Xin Yan (Nanyang Technological University, 2024)
While postpartum depression (PPD) affects around 15% of mothers in Singapore, the knowledge levels are still low and highly stigmatised in Singapore. Beyond Baby Blues, a health communications campaign, aims to empower postnatal Singaporean mothers within one year of childbirth in recognising PPD symptoms and seeking help early. Guided by the Health Belief Model (HBM), the campaign is centered on enhancing knowledge of PPD, encouraging positive attitudes towards seeking help, and nudging those who are facing PPD symptoms to seek help, whether with professionals or their loved ones. Qualitative data from focus group discussions were collected to determine their current levels of knowledge, perceived severity and susceptibility, benefits, barriers and self-efficacy regarding seeking help to formulate the campaign’s strategy. Key findings point to the need for filling knowledge gaps regarding PPD, and to address barriers that lower a mother’s confidence in seeking PPD help resources. These structured the campaign’s content pillars of Educate, Community and Inspire. Key tactics include presence on social media platforms such as Instagram, Facebook and Telegram, an interactive map, ‘Garden of Support’, for mothers to confide or share support with others, distribution of mummy guidebooks and a self-care art workshop to encourage them to take small steps in prioritising themselves. The campaign was evaluated through a quantitative post-campaign survey and the impact and output objectives were evaluated, which concluded limited effectiveness toward attitudinal and behavioural changes. The paper concludes with the campaign’s novelty and limitations and recommendations for future initiatives aimed at addressing PPD among Singaporeans.